1976
DOI: 10.1073/pnas.73.5.1389
|View full text |Cite
|
Sign up to set email alerts
|

Spectroscopic studies and a structural model for blue copper centers in proteins.

Abstract: Distorted tetrahedral Cu(II) should exhibit d-d transitions well below 10,000 cm1, assuming that the ligand field is not unusually strong. We have undertaken, therefore, a detailed investigation of the near-infrared absorption, CD, and magnetic circular dichroism (MCD) spectra of stellacyanin, plastocyanin, and azurin. Detailed analysis of these and analogous visible spectral data has allowed assignments to be made of both the d-d and charge transfer transitions. Interpretation of the charge transfer spectra h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
88
0

Year Published

1979
1979
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(92 citation statements)
references
References 30 publications
4
88
0
Order By: Relevance
“…Thus the blue copper absorption spectrum has historically been assigned as band 6 being the cysteine IT and band 4 the cysteine o+Cu(II) dX2.y2 charge transfer transitions. (27) Significant insight into this possible assignment came from LT MCD data(l9) shown at the bottom of Fig. 4A.…”
Section: A(14)mentioning
confidence: 99%
“…Thus the blue copper absorption spectrum has historically been assigned as band 6 being the cysteine IT and band 4 the cysteine o+Cu(II) dX2.y2 charge transfer transitions. (27) Significant insight into this possible assignment came from LT MCD data(l9) shown at the bottom of Fig. 4A.…”
Section: A(14)mentioning
confidence: 99%
“…[36][37][38] This orbital exhibits a large and highly anisotropic degree of covalency. X-ray absorption spectroscopy (XAS) at the S K-edge 39 and Cu L-edge 40 has indicated that the HOMO contains 38% S(Cys) character and only ∼40% Cu character, and electronic structure calculations 41 indicate that only ∼4% N(His) character is present in the HOMO (because the Cu-S(Met) bond is oriented approximately perpendicular to the HOMO, no S(Met) character is present in the HOMO).…”
Section: Introductionmentioning
confidence: 99%
“…The SEM image of the complexes confirms the presence of ligands in the metalchelates. Hence, the metal ion affects the morphology of Schiff base in the metal-chelates [28][29][30].…”
Section: Resultsmentioning
confidence: 99%